Genetic mapping with Tn5-derived auxotrophs of Caulobacter crescentus. - Barrett, J T (1982)
Chromosomal insertions of Tn5 in Caulobacter crescentus displayed complete stability upon transduction and proved useful in strain building on complex media. RP4-primes constructed in vitro containing C. crescentus genomic sequences in the HindIII site of the kanamycin resistance gene failed to show enhanced or directed chromosome mobilization abilities. One of these kanamycin-sensitive RP4 derivatives, pVS1, was used as a mobilization vector in conjugation experiments on complex media where chromosomal Tn5 transfer to the recipient was selected. pVS1-mediated transfer of Tn5-induced auxotrophic mutations occurred at frequencies of 10(-6) to 10(-8) per donor cell. During conjugation with Tn5-encoded kanamycin resistance as the selected marker, Tn5 remained in its donor-associated locus in 85 to 100% of the transconjugants. A collection of eight temperature-sensitive donor strains bearing Tn5 insertion mutations from various regions of the C. crescentus genetic map were used to provide a rapid means for the determination of the map location of a new mutation. Use of the techniques described in this paper allowed an expansion of the C. crescentus genetic map to include the relative locations of 32 genes.